Understanding Housing Affordability in Australia - Cho, Yunho; Li, Shuyun May; Uren, Lawrence (My University, 2021)
We evaluate housing affordability in Australia particularly as it relates to the ability of households to purchase a home. An overview of trends in the Australian housing market is provided with a discussion of rising house prices and falling home ownership. We then provide an estimate of the fundamental price of housing at capital-city level based upon the user cost of housing. We also discuss policies that have been used and policies that could be used to improve housing affordability. We conclude with a brief discussion of the long term barriers to housing affordability.
The Australian Economic Review
Keywords: Housing, communities and neighbourhoods